ANALYSES OF BROILER CHICKEN’S MARKETING IN TRADITIONAL MARKET OF MEDAN CITY - Yusrizal Fachri; A Hakim Daulay; Nevy Diana Hanafi; M Tafsin; E Mirwandhono (Talenta Publisher, 2017)
The purpose of this research is to identify the characteristics of marketing institutions, marketing chain, marketing function, and analyze added value in broiler marketing institutions in traditional market of Medan City from April until May 2017. This research used primary and secondary data that obtained from observation and interview of respondents and also the related agencies. The location of the research was determined purposively method and determination of respondents with accidental sampling method that has 99 respondents. The data analysis by descriptive analyses and added value analyses. The results showed the characteristic of respondents were dominated by male sex (72,75%) with an experience of 11-20 years (56,19%) with 6-10 employees (47,99%), aged 41-50 years (57,99%) and had senior high school education level / equal (45,34%). There were five kinds of marketing chains where the biggest marketing chains that was marketing chains broiler farmers to collectors then to slaughterers at once retailers with life broiler chicken input then become carcass product to retailers and to consumers. The exchange function and the facility function are done by each marketing institution, processing on the physical function is not found in the collectors level. The highest added value was found in slaughterers at once retailers Rp 9.178,72. Meanwhile, the lowest added value in collectors was Rp 898,55. The conclusion, the biggest marketing chain involved all the marketing institutions so the bigger the marketing margin that is formed the more profitable they are, but the higher the price the consumer pays. The shorter the marketing chain the more it gives a big profit to broiler farmers.